Microwave dielectric properties of ultra-low loss Li2MgTi0.7(Mg1/3Nb2/3)0.3O4 ceramics sintered at low temperature by LiF addition. Issue 11 (1st August 2018) - Yang, Y.K.; Liu, F.L.; Zhang, Y.W.; Li, M.F.; Ling, F.; Wu, H.T.
Abstract: In this work, ultra-low loss Li2 MgTi0.7 (Mg1/3 Nb2/3 )0.3 O4 ceramics were successfully prepared via the conventional solid-state method. X-ray photoelectron spectroscopy (XPS), thermally stimulated depolarization current (TSDC) and bond energy were used to determine the distinction between intrinsic and extrinsic dielectric loss in (Mg1/3 Nb2/3 ) 4+ ions substituted ceramics. The addition of (Mg1/3 Nb2/3 ) 4+ ions enhances the bond energy in unit cell without changing the crystal structure of Li2 MgTiO4, which results in high Q·f value as an intrinsic factor. The extrinsic factors such as porosity and grain size influence the dielectric loss at lower sintering temperature, while the oxygen vacancies play dominant role when the ceramics densified at 1400 °C. The Li2 MgTi0.7 (Mg1/3 Nb2/3 )0.3 O4 ceramics sintered at 1400 °C can achieve an excellent combination of microwave dielectric properties: εr =  16.19, Q·f  = 160, 000 GHz and τ f = −3.14 ppm/°C. In addition, a certain amount of LiF can effectively lower the sintering temperature of the matrix, and the Li2 MgTi0.7 (Mg1/3 Nb2/3 )0.3 O4 -3 wt% LiF ceramics sintered at 1100 °C possess balanced properties with ε r  =  16.32, Q·f  = 145, 384 GHz and τ f = −16.33 ppm/°C.